A refined approach for quantitative kinematic vorticity number estimation using microstructures. (December 2021) - Graziani, Riccardo; Larson, Kyle P.; Law, Richard D.; Vanier, Marc-Antoine; Thigpen, James R.
Abstract: This study proposes a refined approach for quantification of the vorticity of kinematic flow in natural shear zones. This approach, here called C′- c method, is based on estimation of the angle between the flow apophyses A1 and A2 by performing two independent measurements. The tilting angle of a quartz crystallographic preferred orientation (β) and the orientation of the C′ shear bands (θ). Using these two angles it is possible to quantify the sectional vorticity number using the following formula: Wn = Cos[2(θ-β)]. Data obtained by applying the C′- c method on known shear zones well match the vorticity numbers estimated with other approaches on the same structures. In this study, we applied the C′- c method to the Abloviak Shear Zone (Torngat Orogen) and the Ben Hope Thrust (Caledonides of NW Scotland) obtaining the first vorticity data on these structures. Our data show that the C′- c method can increase the potential range of rocks in which it is possible to estimate kinematic vorticity. Our results also show that the C′- c method can be negatively affected by microscale kinematic flow partitioning, highlighting the importance of a detailed microstructure characterization of the studied rocks before any estimate of kinematic vorticity is attempted. Highlights: Quartz CPOs and shear band orientations can be used as a kinematic vorticity gauge. The combined CPO and C′ bands gauge is termed the C′- c method. C′- c results match with vorticity data obtained with other methods on the same rocks. The C′- c method can be used also in presence of GBM and/or annealing in quartz. The C′- c method results can be affected by flow partitioning in quartz.